Plausible crime stories: the legal history of sexual offences in mandate Palestine - Darr, Orna Alyagon (Law in context, 2020)
"Plausible Crime Stories is not only the first in-depth study of the history of sex offences in Mandate Palestine but it also pioneers an approach to the historical study of criminal law and proof that focuses on plausibility. Doctrinal rules of evidence only partially explain which crime stories make sense while others fail to convince. Since plausibility is predicated on commonly held systems of belief, it not only provides a key to the meanings individual social players ascribe to the law but also yields insight into communal perceptions of the legal system, self-identity, the essence of normality and deviance and notions of gender, morality, nationality, ethnicity, age, religion and other cultural institutions. Using archival materials, including documents relating to 147 criminal court cases, this socio-legal study of plausibility opens a window onto a broad societal view of past beliefs, dispositions, mentalities, tensions, emotions, boundaries and hierarchies"--